Testing the Relationship between Financial Ratios and Stock Prices of Listed Companies on the Stock Exchange of Thailand: Before, During and After the COVID-19 Pandemic - Tripattanasit, Pimonwan; Chotkunakitti, Phatnatcha; Suksanguan, Wanrudee; Srithaworn, Wattana; Kobkanjanapued, Yodsawinkan (Arts of Management Journal, 2024)
This study examines the Testing of the Relationship between Financial Ratios and Stock Prices of listed Companies on the Stock Exchange of Thailand: Before, During, and After the COVID-19 Pandemic. The financial ratios analyzed in this research are: 1) Current Ratio (CR), 2) Total Asset Turnover Ratio (TAT) 3) Times Interest Earned (TIE) 4) Debt to Equity Ratio (DE), and 5) Return of Asset (ROA). This study collected a sample listed on the Stock Exchange of Thailand between 2018 and 2022 a total of 5 years with 3,198 datasets from the Stock Exchange of Thailand database. The data were analyzed using Descriptive Statistics, Pearson Correlation Coefficient Analysis, and Inferential Statistics by Ordinary Least Analysis: OLS. The results showed that 1) The Current Ratio, Total Asset Turnover, Times Interest Earned, and Return of Asset ratio positively affected stock prices. As for the Debt to debt-equity ratio, it has a negative effect on the stock prices. 2) The Testing of the Relationship between Financial Ratios and Stock Prices during the COVID-19 pandemic found that Return on total assets (ROA) during the COVID-19 outbreak is related to stock prices being lower than before the COVID-19 outbreak. Statistically significant at the 0.01 level. 3) The Testing of the Relationship between Financial Ratios and Stock Prices after the COVID-19 pandemic found that Return on total assets (ROA) after the COVID-19 outbreak is associated with an increase in stock prices more than during the COVID-19 outbreak.